SOCIAL DIALOGUE AND TOLERANCE: BUILDING A MORE JUST AND DEMOCRATIC SOCIETY IN MEXICO - Aragón, Iliana Josefina Velasco; Rodríguez, María Asunción Gutiérrez; Montoya, Miriam Angelica Catalina Salcedo; Altieri, Ileana Margarita Simancas; Jiménez, Roberto Chiquete; Rivas, Luis Ricardo Rodríguez; Chacón, Tatewari López; Chávez, Héctor Vicente Cisneros; Hernández, Jorge Alberto González; Foster, Paulo Alejandro González; Haro, Tania Maricela Aguilar; Herrera, Gabriel Carrillo (Seven Editora, 2025)
This analysis seeks to examine the causes that have contributed to the decreasing tolerance in dialogue among different sectors and social classes in Mexico. The study was conducted using a qualitative, analytical, and documentary approach, offering a comprehensive perspective on the dynamics that influence social coexistence. It identifies the causes of intolerance and also analyzes the role of the political class and the media in constructing narratives that negatively affect social understanding, dialogue, and harmonious coexistence among citizens. The findings of this research are expected to be useful both for scholars and for those who design public policies and strategies aimed at fostering greater peaceful coexistence in the country, particularly in times when violence has taken over much of the public spaces in the Mexican Republic.DOI: https://doi.org/10.56238/sevened2025.036-100